Membangun Loyalitas Online: Pengaruh Kepercayaan Merek, Keterikatan Merek dan Penerimaan Teknologi - Dessy Yunita; Ahmad Nazaruddin; Lisnawati (Universitas Medan Area, 2023)
Technological developments change the mode of retail business. Initially, the company relied on traditi-onal channels (brick and mortar), then changed to online-based channels (brick and click). These changes affect customer behavior towards retail. Loyalty that has been built in traditional retail with a single channel is expected to be able to form online loyalty in multi-channel retail. Brand trust, brand attach-ment, and technology acceptance are considerations that influence online loyalty. The population are The Body Shop (TBS) buyers who have made purchases in stores and online channels. The sampling method uses non probability sampling and the sample selection uses purposive sampling, which is selected accord-ing to research needs. The data collection method was in the form of distributing 200 questionnaires. The analysis technique uses structural equation modeling to examine the relationships and influences between variables. The statistical analysis use SPSS version 22 and AMOS version 22 were used. The research results showed that brand trust, brand attachment had a positive significant effect on offline loyalty, offline loyalty had a positive significant effect on online loyalty and technology acceptance had no positive significant effect on online loyalty. Then, offline loyalty is not proven to mediate between brand trust and online loyalty and offline loyalty is not proven to mediate between brand attachment and online loyalty